2019
DOI: 10.1111/dom.13673
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetes Unmet Need with Basal Insulin Evaluation (DUNE) study in type 2 diabetes: Achieving HbA1c targets with basal insulin in a real‐world setting

Abstract: Aims To describe in a real‐world setting the achievement of physician‐selected individualized HbA1c targets in individuals with type 2 diabetes, newly or recently initiated with basal insulin, and the association of hypoglycaemia with target achievement. Materials and methods A 12‐week, prospective, single‐arm, observational study of adults with type 2 diabetes, either newly initiated with any basal insulin or start on basal insulin within the preceding 12 months. At enrollment, eligible participants from 28 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
1
22
0
4
Order By: Relevance
“…The complementary nature of the combined agents, the simplicity of administration and titration, and the reduction in side effects contribute to the greater effectiveness of the fixed-ratio combination. 10,11 The average effective insulin dose in Japanese patients is generally lower than in the West, 12,13 with the pathophysiology of T2DM driven by relative insulin deficiency rather than insulin resistance. Japanese patients generally respond well to dipeptidyl peptidase-4 (DPP-4) inhibitors and GLP-1 RAs.…”
Section: Introductionmentioning
confidence: 99%
“…The complementary nature of the combined agents, the simplicity of administration and titration, and the reduction in side effects contribute to the greater effectiveness of the fixed-ratio combination. 10,11 The average effective insulin dose in Japanese patients is generally lower than in the West, 12,13 with the pathophysiology of T2DM driven by relative insulin deficiency rather than insulin resistance. Japanese patients generally respond well to dipeptidyl peptidase-4 (DPP-4) inhibitors and GLP-1 RAs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the clinical benefits favouring second‐generation versus first‐generation BIs, including lower rates of hypoglycaemia, RWE suggests that patients are still not achieving glycaemic targets during the initial 12 weeks of treatment. For example, the DUNE study, a prospective, 12‐week real‐world observational study in insulin‐naïve and pretreated (within the preceding 12 months) individuals with T2D who initiated or switched BI therapy, showed that only 28% and 27% of these patients, respectively, achieved their individualized HbA1c targets . Failure to achieve these targets could have been because of insufficient dose titration, as only modest increases in dose were observed (mean 0.10 U/kg in insulin‐naïve patients and 0.06 U/kg in pretreated patients).…”
Section: Can Newer Bi Analogues Assist With Insulin Titration and Trementioning
confidence: 99%
“…The inclusion of this parameter could change the perspective of the HbA1c results substantially. In the DUNE study [6], individualized HbA1c targets were set up by patients’ physicians or the study experts according to international guidelines [7] into several groups: < 7% for 18% of patients, 7.0 to < 7.5% for 57%, 7.5 to < 8.0% for 17% and ≥ 8.0% for 6.8% of patients.…”
Section: Treatment Targets Achievement Studiesmentioning
confidence: 99%